Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1016/j.ymeth.2007.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microRNA expression by in situ hybridization with RNA oligonucleotide probes

Abstract: In situ hybridization is an important tool for analyzing gene expression and developing hypotheses about gene functions. The discovery of hundreds of microRNA (miRNA) genes in animals has provided new challenges for analyzing gene expression and functions. The small size of the mature miRNAs (∼20-24 nucleotides in length) presents difficulties for conventional in situ hybridization methods. However, we have developed a modified in situ hybridization method for detection of mammalian miRNAs in tissue sections, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 30 publications
(41 reference statements)
0
66
0
Order By: Relevance
“…Up to now, there were three different ways reported to detect mature miRNAs by ISH. Robert and David described a modified ISH method for miRNAs detection with RNA probes, in combination with specific wash conditions based on tetramethylammonium chloride and RNase A treatment to generate highly sequence specific conditions [27]. While this work was in progress, Obernosterer et al [28] reported another ISH method, which focused on the use of LNA that allowed a significant increase in the hybridization temperature and thereby an enhanced stringency for short probes as required for miRNA detection.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, there were three different ways reported to detect mature miRNAs by ISH. Robert and David described a modified ISH method for miRNAs detection with RNA probes, in combination with specific wash conditions based on tetramethylammonium chloride and RNase A treatment to generate highly sequence specific conditions [27]. While this work was in progress, Obernosterer et al [28] reported another ISH method, which focused on the use of LNA that allowed a significant increase in the hybridization temperature and thereby an enhanced stringency for short probes as required for miRNA detection.…”
Section: Discussionmentioning
confidence: 99%
“…ISH probes were generated from RNA oligonucleotides (Invitrogen, Carlsbad, CA) with minor changes to the labeling reaction as follows: 0.75 l T4 DNA Kinase, 1 l 10ϫ Polynucleotide Kinase Buffer (Affymetrix, Santa Clara, CA), 2 l RNA (20 pmol/l), and 6.25 l 33 P-␥ATP (Perkin Elmer, Waltham, MA) and incubated at 37°C for 30 min (45). Antisense and control (two interior mismatched nucleotides) RNA oligonucleotides (Invitrogen) were synthesized based on sequences obtained from miRBase.org and hybridization specificity as determined through comparative ISHs failing to yield autoradiographic signal above background (Fig.…”
Section: Mirna Ishmentioning
confidence: 99%
“…60,[138][139][140][141][142][143][144] In situ hybridization detection of microRNAs has also been reported by several groups. [145][146][147] It is noteworthy that standard formalin-fixation and paraffin-embedding of tissues seems to preserve microRNAs in a reasonably intact and extractable state. 146,148,149 Once these tools are clinically validated more extensively, they should enable microRNA measurements to become a part of the pathologist's diagnostic armamentarium.…”
Section: Practical Aspectsmentioning
confidence: 99%